Cutaneous Leishmaniasis on the Glans Penis: A Case Report - Farhad Handjani; Kaveh Taghipour; Amir Miri (Pasteur Institute of Iran, 2019)
A 79-year-old male presented with an ulcerated lesion on the glans penis. Histopathological evaluation of the biopsy from the lesion revealed the presence of Leishmania amastigotes and confirmed the diagnosis of cutaneous leishmaniasis. The patient was treated with several sessions of cryotherapy; the lesion healed and left no scar.